ID: 120. Issue 4 (April 2016) - Shaaya, M; Fu, P; Karginov, A; Natarajan, V
Abstract : Pulmonary edema is a hallmark of several diseases including acute respiratory distress syndrome (ARDS) and is characterized by the disruption of the pulmonary endothelial barrier at its early stage. Maintaining the integrity of the adherens junctions (AJs) by stabilizing VE-Cadherin (VEC) at the cell membrane after injury could potentially be important to minimize endothelial barrier disruption. Since Phospholipase D (PLD) and its catalytic product, phosphatidic acid (PA), has been shown to be critical in membrane trafficking and in recycling of a number of cell surface receptors, we hypothesized that PLD/PA pathway accelerates the rate of VEC recycling to the lamellipodia to reassemble the AJs. We demonstrate, by measuring the trans endothelial resistance of human lung microvascular endothelial cells (HLMVECs), that inhibiting PLD2-dependent PA production increases the endothelium permeability in response to thrombin. Furthermore, immunostaining shows that the uniform redistribution of VEC to the AJs post thrombin insult is compromised when PLD-dependent PA production is inhibited, and resulted in the appearance of eminent intercellular gaps. Also, PLD2 inhibition prevented the HLMVECs from fully spreading after thrombin stimulation while the protrusive activity remained unaffected, suggesting that PLD2 is not required by HLMVECs to send protrusions, but is critical for the adherence of the protrusions. LPS-induced lung injury was more severe in PLD2 knockout mice compared to WT in an in vivo ARDS model. These observations suggest that PLD/PA signaling plays an important role in resealing of endothelial gaps post LPS-induced lung injury and could potentially be therapeutically utilized to enhance post-injury endothelium recovery.